Financing mechanisms applied for successful Universal Health Coverage in Malaysia, Thailand and Singapore - Lessons for Pakistan - Jabeen , Rawshan; Unaib Rabbani; Nazish Abbas (Journal of the Pakistan Medical Association, 2021)
Background: Universal Health Coverage (UHC) is a global health agenda in which health care financing plays a vital role. This paper presents an overview of the provision of health insurance in three countries: Malaysia, Thailand and Singapore who have achieved universal health coverage. In the current scenario of Pakistan’s health sector, achieving universal health coverage is a challenge because of human resource constraints, lack of institutional capacities, poor operationalizing and very low allocation of Gross Domestic Product for health. Online databases were used to collect the information. We used databases such as; Google scholars and PubMed and World Bank web site to retrieve relevant literature. CONTINUOUS...